Search of the flow curve of shock-resistant polystyrene, not invariant concerning hydraulic radius of 8х32мм channel - Сівецький, Володимир Іванович; Рябінін, Дмитро Дмитрович; Сокольський, Олександр Леонідович; Кривко, Сергій Антонович; Наді, Амір (Eastern-European Journal of Enterprise Technologies, 2012)
In article the method of the curves current polymers is offered, not invariant concerning hydraulic radius of the channel, in particular in channel 8x32 mm, for use possibility the viscosimetry data is offered at calculations of not round channels